Enrichment efficiency of lutein in eggs and its function in improving fatty liver hemorrhagic syndrome in aged laying hens - Dieudonné M. Dansou; Han Chen; Yanan Yu; Youyou Yang; Isabelle N. Tchana; Liyuan Zhao; Chaohua Tang; Qingyu Zhao; Yuchang Qin; Junmin Zhang (Poultry Science, 2024)
ABSTRACT: In this study, we evaluated the enrichment efficiency of lutein in eggs and its function in preventing fatty liver hemorrhagic syndrome (FLHS) in aged laying hens. Five groups of laying hens (65 wk old) were fed basal diets supplemented with 0, 30, 60, 90, or 120 mg/kg of lutein. The supplementation period lasted 12 wk followed by 2 wk of lutein depletion in feed. The results revealed that lutein efficiently enriched the egg yolks and improved their color with a significant increase in relative redness (P < 0.001). Lutein accumulation increased in the egg yolk until day 10, then depletion reached a minimum level after 14 d. Overall, zeaxanthin content in all the groups was similar throughout the experimental period. However, triglycerides and total cholesterol were significantly decreased in the liver (P < 0.05) but not significantly different in the serum (P > 0.05). In the serum, the lipid metabolism enzyme acetyl-CoA synthetase was significantly reduced (P < 0.05), whereas dipeptidyl-peptidase 4 was not significantly different (P > 0.05), and there was no statistical difference of either enzyme in the liver (P > 0.05). Regarding oxidation and inflammation-related indexes, malondialdehyde, tumor necrosis factors alpha, interleukin-6, and interleukin-1 beta were decreased, whereas superoxide dismutase and total antioxidant capacity increased in the liver (P < 0.001). The function of lutein for the same indexes in serum was limited. It was concluded that lutein efficiently enriched the egg yolk of old laying hens to improve their color and reached the highest level on day 10 without being subject to a significant conversion into zeaxanthin. At the same time, lutein prevented liver steatosis in aged laying hens by exerting strong antioxidant and anti-inflammatory functions, but also through the modulation of lipid metabolism, which may contribute to reducing the incidence of FLHS in poultry.